Tipologias dos bancos no Brasil - Forte, Sérgio Henrique Arruda Cavalcante (1995)
The purpose of this work was to contribute for better understanding of banking branch in Brazil, by making a research to identify the types of banks existing into brazilian financiaI system. As a result of the research there types of banking standardizations were exposed: structural: more traditional, very often present in the language and laws of banking authorities and of banks themselves; Marketing Oriented: more recent, used more often by experts in banking industry, basically structured by the classification of whole sales and retail banks. We tryed to go beyond these two categorizations, and strategic: still embryonary, exposed as a contribution to a better deepening of the banks strategical conception, in order to help banking market, the costumers, and even the banking authority itself about this new approach for the improvement of decision taking and the design of a brazilian financiaI system. As a theorical basis we used foundations and topical strategies approachs in Business Strategy. Specifically the types of business strategies and strategic groups indentification were researched. As an empirical focus we chose banking branch in Brazil, and as methodology the exploratory methodology. The time range of the analysis begins at the time of the law of creation of the multiple banks (September/94) and ends in June/94, opening a wider field for discussion about strategies and strategical classification of banks in Brazil.